The contribution of business ownership in bringing down unemployment in Japan - André J. van Stel; A. Roy Thurik; Ingrid Verheul; Lendert Baljeu (Max Planck Institute of Economics, 2006)
The relationship between entrepreneurship, measured by fluctuations in the business ownership rate, and unemployment in Japan is examined for the period 1972-2002. We conclude that, although Japan's unemployment rate has been influenced by different exogenous shocks as compared to other OECD countries, the effects of entrepreneurship on unemployment are not distinct. In the past small firms in Japan benefited from the protective environment of the keiretsu structure. This secure environment no longer exists, and a new market environment conducive to new venture creation and growth is not yet established. We argue that the Japanese government should actively stimulate an entrepreneurial culture.
More recent version: http://hdl.handle.net/10419/111000
Keywords: L11; M13; O53; 330; entrepreneurship; business ownership; unemployment; Japan